An update on red blood cell storage lesions, as gleaned through biochemistry and omics technologies. Issue 1 (6th August 2014) - D'Alessandro, Angelo; Kriebardis, Anastasios G.; Rinalducci, Sara; Antonelou, Marianna H.; Hansen, Kirk C.; Papassideri, Issidora S.; Zolla, Lello
<x xml:space="preserve">Abstract</x> Red blood cell (RBC) aging in the blood bank is characterized by the accumulation of a significant number of biochemical and morphologic alterations. Recent mass spectrometry and electron microscopy studies have provided novel insights into the molecular changes underpinning the accumulation of storage lesions to RBCs in the blood bank. Biochemical lesions include altered cation homeostasis, reprogrammed energy, and redox metabolism, which result in the impairment of enzymatic activity and progressive depletion of high‐energy phosphate compounds. These factors contribute to the progressive accumulation of oxidative stress, which in turn promotes oxidative lesions to proteins (carbonylation, fragmentation, hemoglobin glycation) and lipids (peroxidation). Biochemical lesions negatively affect RBC morphology, which is marked by progressive membrane blebbing and vesiculation. These storage lesions contribute to the altered physiology of long‐stored RBCs and promote the rapid clearance of up to one‐fourth of long‐stored RBCs from the recipient's bloodstream after 24 hours from administration. While prospective clinical evidence is accumulating, from the present review it emerges that biochemical, morphologic, and omics profiles of stored RBCs have observable changes after approximately 14 days of storage. Future studies will assess whether these in vitro observations might have clinically meaningful effects.